Short-term and long-term plasticity in the visual-attention system: Evidence from habituation of attentional capture - Turatto, Massimo; Pascucci, David (Neurobiology of learning and memory, 2016)
•Attentional capture by sudden visual onsets is subject to habituation.•Both short-term and long-term habituation of attentional capture was observed.•Habituation can make the visual-attention system fully immune to distraction.•Spontaneous recovery of capture emerged when the distractor was temporarily removed.•Neural plasticity can affect high-order cognitive functions. Attention is known to be crucial for learning and to regulate activity-dependent brain plasticity. Here we report the opposite scenario, with plasticity affecting the onset-driven automatic deployment of spatial attention. Specifically, we showed that attentional capture is subject to habituation, a fundamental form of plasticity consisting in a response decrement to repeated stimulations. Participants performed a visual discrimination task with focused attention, while being occasionally exposed to a distractor consisting of a high-luminance peripheral onset. With practice, short-term and long-term habituation of attentional capture emerged, making the visual-attention system fully immune to distraction. Furthermore, spontaneous recovery of attentional capture was found when the distractor was temporarily removed. Capture, however, once habituated was surprisingly resistant to spontaneous recovery, taking from several minutes to days to recover. The results suggest that the mechanisms subserving exogenous attentional orienting are subject to profound and enduring plastic changes based on previous experience, and that habituation can impact high-order cognitive functions.